2008
DOI: 10.1111/j.1447-0756.2008.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde, nitric oxide and adrenomedullin levels in patients with primary dysmenorrhea

Abstract: In conclusion, the results of this study showed that the serum levels of MDA, NO, and AM increase in subjects with primary dysmenorrhea, suggesting the possibility that lipid peroxidation and oxidative stress play a significant role in the etiopathogenesis of primary dysmenorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 16 publications
2
43
0
Order By: Relevance
“…AS has been used to regulate menstruation, an inflammatory syndrome, in Asia for thousands of years. Inflammatory mediators, such as PGE 2 [3], NO [4] and TNF-α [5], are elevated in the serum and peritoneal fluid of primary dysmenorrheal subjects. NF-κB is thought to promote and maintain endometriosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…AS has been used to regulate menstruation, an inflammatory syndrome, in Asia for thousands of years. Inflammatory mediators, such as PGE 2 [3], NO [4] and TNF-α [5], are elevated in the serum and peritoneal fluid of primary dysmenorrheal subjects. NF-κB is thought to promote and maintain endometriosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Dysmenorrhea also has been reported to lead to an increase in lipid peroxidation, an index of oxidative stress (8). Previous studies about OS and dysmenorrhea investigated only malondialdehyde (MDA) levels as a marker of oxidative status (9,10). However, measuring MDA levels is limited in detecting oxidative stress in some cases, and might not be sufficient to show real oxidative stress in dysmenorrhoea (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…When a bacterial infection occurs, increased [Ca 2+ ] i due to release from intracellular stores and entry into neutrophils via VGCC and TRP channels is a key initiator of activation, leading to increased ROS production and providing a means of attacking the bacteria (Dikensoy et al, 2008;Bréchard and Tschirhart, 2008). In chronic inflammatory disease, however, this mechanism contributes to the development of oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of proinflammatory cytokines, interleukins (Yeh et al, 2004), and tumor necrosis factor-␣ (TNF-␣), neutrophil hyperfunction (Marchini et al, 1995), and excessive reactive oxygen species (ROS) production (Marchini et al, 1995;Dikensoy et al, 2008) have been reported in patients with primary dysmenorrhea. Neutrophils are cells that play an important role in immune responses (Ayub and Hallett, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation